Environmental ethics of Kuta traditional village community in preserving the environment and its future prospects - Nisa, Ainun; Surtikanti, Hertien Koosbandiah (Interaction, Community Engagement, and Social Environment, 2024)
Environmental conservation is a major global issue, with Indonesia ranking low in the Environmental Performance Index 2022. This study focuses on Kampung Adat Kuta, a community in Ciamis, West Java, which upholds local wisdom in maintaining the balance of nature as one of the sustainable environmental ethics and its future prospects. The methods used in this research are literature study and bibliometric analysis. The results show that customary rules, such as respecting sacred forests, building houses according to the rules of the ancestors, and the prohibition of making wells, reflect local wisdom that supports environmental conservation. The people of Kampung Adat Kuta also uphold the concept of "pamali" as a norm to prevent potential environmental hazards. In addition, the results of bibliometric analysis show that the prospect of research related to environmental ethics in the community of Kampung Adat Kuta is still very broad. The bibliometric analysis resulted in four thematic clusters that reflect the complexity of environmental ethics issues in Kampung Adat Kuta involving aspects of sustainability, local values, and community participation. Overall, environmental ethics in Kampung Kuta help maintain the balance of nature and make a positive contribution to the sustainability of natural resources. Although further research is needed, these findings highlight the importance of local values in responding to the challenges of the environmental crisis and offer valuable insights for the development of environmental conservation policies at the local and national levels.